Extracellular Vesicles for the Diagnosis of Cancers. Issue 1 (7th December 2021) - Xue, Yuxiang; Feng, Xue; Fan, Xianfeng; Zhu, Guangyu; McLaughlan, James; Zhang, Wenjun; Chen, Xianfeng
Abstract : Extracellular vesicles (EVs) are ultrasmall structures secreted by various types of cells and carry biomarkers such as DNA, RNA, and the protein of the cells that secreted them. Cancer cell‐derived EVs can be detected at the very early stage of cancers, and hence the use of EVs for cancer diagnosis has aroused significant interest. This review summarizes the representative strategies of using EVs as biomarkers to detect different types of cancers, evaluates their advantages and challenges, and discusses their development prospects for cancer early diagnosis. Abstract : Cancer cell‐derived extracellular vesicles (EVs) can be detected at the very early stage of cancers, and hence the use of EVs for cancer diagnosis has aroused significant interest. This review summarizes the representative strategies of using EVs as biomarkers to detect different types of cancers, evaluates their advantages and challenges, and discusses their development prospects for cancer early diagnosis.